Animation Orientation 2025: Building community, creativity and confidence by the beach - Natasha, Rusdy Wong; Tang, Hung Moi; Jong, Sze Joon; Loh, Ngiik Hoon; Terry, Lucas; Syaryfah Fazidawaty, Wan Busrah; Auzani Zeda, Mohamed Kassim (Faculty of Applied and Creative Arts, Universiti Malaysia Sarawak, 2025)
The Animation Orientation 2025 was held from 8 to 9 November 2025 at Dynawood Beach Stay & Resort, Sematan, Lundu, bringing together around 45 first-year students for two days of teamwork, creativity, and meaningful connection. This annual programme is designed to welcome new students into the Animation family while fostering the collaborative spirit essential to their journey in the creative arts.